Gender differences in the effect of adult amphetamine on cognitive functions of rats prenatally exposed to methamphetamine - Macúchová, E; Nohejlová, K; Slamberová, R (Behavioural brain research, 2014)
Psychostimulants have been shown to affect brain regions involved in the process of learning and memory consolidation. It has been shown that females are more sensitive to the effects of drugs than males. The aim of our study was to investigate how prenatal methamphetamine (MA) exposure and application of amphetamine (AMP) in adulthood would affect spatial learning of adult female and male rats. Mothers of the tested offspring were exposed to injections of MA (5mg/kg) or saline (SA) throughout the entire gestation period. Cognitive functions of adult rats were evaluated in the Morris Water Maze (MWM) tests. Adult offspring were injected daily with AMP (5mg/kg) or SA through the period of MWM testing. Our data from the MWM tests demonstrates the following. Prenatal MA exposure did not change the learning ability of adult male and female rats. However, AMP administration to adult animals affected cognitive function in terms of exacerbation of spatial learning (increasing the latency to reach the hidden platform, the distance traveled and the search error) only in female subjects. There were sex differences in the speed of swimming. Prenatal MA exposure and adult AMP treatment increased the speed of swimming in female groups greater than in males. Overall, the male subjects showed a better learning ability than females. Thus, our results indicate that the adult AMP treatment affects the cognitive function and behavior of rats in a sex-specific manner, regardless of prenatal exposure.
Keywords: Prenatal Exposure Delayed Effects; Male; Rats, Wistar; zpožděný efekt prenatální expozice; Maze Learning; sexuální faktory; Pregnancy; těhotenství; Age Factors; mužské pohlaví; potkani Wistar; Spatial learning; Estrous cycle; krysa rodu Rattus; bludiště - učení; Central Nervous System Stimulants; methamfetamin; kognice; stimulanty centrálního nervového systému; Animals; Methamphetamine; amfetamin; ženské pohlaví; zvířata; Sex Factors; Memory; Rats; věkové faktory; prostorové chování; Amphetamine; Spatial Behavior; Morris Water Maze; Female; Cognition